2004
DOI: 10.1037/0022-3514.87.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Taking as Egocentric Anchoring and Adjustment.

Abstract: The authors propose that people adopt others' perspectives by serially adjusting from their own. As predicted, estimates of others' perceptions were consistent with one's own but differed in a manner consistent with serial adjustment (Study 1). Participants were slower to indicate that another's perception would be different from--rather than similar to--their own (Study 2). Egocentric biases increased under time pressure (Study 2) and decreased with accuracy incentives (Study 3). Egocentric biases also increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
923
3
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,063 publications
(998 citation statements)
references
References 48 publications
63
923
3
9
Order By: Relevance
“…These experiments extend other demonstrations that people have difficulty discounting "top-down" effects on the perception of degraded auditory stimuli (e.g., Epley, Keysar, Van Boven, & Gilovich, 2004;Lange, Thomas, Dana, & Dawes, 2011;Vokey & Read, 1985).…”
Section: Auditory Hindsight Biassupporting
confidence: 84%
“…These experiments extend other demonstrations that people have difficulty discounting "top-down" effects on the perception of degraded auditory stimuli (e.g., Epley, Keysar, Van Boven, & Gilovich, 2004;Lange, Thomas, Dana, & Dawes, 2011;Vokey & Read, 1985).…”
Section: Auditory Hindsight Biassupporting
confidence: 84%
“…A comparison of the gaze pattern of participants who listened to a non-native speaker with those who listened to a native speaker revealed that, indeed, participants were more attuned to the perspective of the director when she was a non-native speaker (Lev-Ari, Barr and Keysar, under review). This effect was found despite the fact that listening to non-native speakers imposes a cognitive load, and added cognitive load in general leads to worse perspective taking (Epley et al 2004). This study thus shows that adjustment in allocation of attention during language processing can have non-linguistic social consequences.…”
Section: Social Consequencesmentioning
confidence: 93%
“…Indeed, studies have found that enduring stressful, anxiety-inducing events-and the subjective experience of uncertainty that accompanies such events-can increase reliance on self-generated numeric anchors (Inbar & Gilovich, 2011; see also Kassam, Koslov, & Mendes, 2009). Given the substantial overlap in processes underlying adjustment from self-generated numeric anchors when making numeric judgments (Epley & Gilovich, 2001) and processes underlying adjustment from accessible self-knowledge when reasoning about others' mental states (Epley et al, 2004), it stands to reason that anxiety may operate similarly during mentalstate reasoning as when making numeric judgments.…”
Section: Anxiety and Mental-state Reasoningmentioning
confidence: 99%